Effect of Fluoride Varnishes on Demineralization and Acid Resistance in Subsurface Demineralized Lesion Models - Rika Iwawaki; Taku Horie; Abdulaziz Alhotan; Yuka Nagatsuka; Keiko Sakuma; Kumiko Yoshihara; Akimasa Tsujimoto (Journal of Functional Biomaterials)
This study aimed to clarify the effects of high-concentration fluoride varnish application on the inhibition of the progression of initial enamel caries. Remineralization capacity and acid resistance following high-concentration fluoride varnish application were compared with untreated models and models treated with fluoride mouthwash. Bovine enamel was used to create a model of initial enamel caries. The high-concentration fluoride varnishes Enamelast and Clinpro White Varnish and the fluoride mouthwash Miranol were used. Specimens were evaluated using Contact Microradiography (CMR) and an Electron Probe Micro-Analyzer (EPMA). While a single application of high-concentration fluoride varnish and short-term fluoride mouthwash use did not appear to cause remineralization in the subsurface demineralized layer, improvements in acid resistance were observed, leading to reduced demineralization under subsequent acidic challenges.